2022
DOI: 10.3847/1538-4357/ac8164
|View full text |Cite
|
Sign up to set email alerts
|

CARAMEL-gas: A Step toward Fast Empirical Models of the Broad-line-emitting Gas

Abstract: Fast empirical models of the broad emission line region (BLR) are a powerful tool to interpret velocity-resolved reverberation mapping (RM) data, estimate the mass of the supermassive black holes, and gain insight into its geometry and kinematics. Much of the effort so far has been devoted to describing the emissivity of one emission line at a time. We present here an alternative approach aimed at describing the underlying BLR gas distribution, by exploiting simple numerical recipes to connect it with emissivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In contrast, CARAMEL utilizes a more prescriptive parameterization of BLR properties. For example, CARAMEL treats the clouds as particles that are representative of a gas density field and approximates the responding emission by setting the emissivity as a radial power-law function (Williams & Treu 2022). CARAMEL includes a parameter estimation procedure to recover the best-matching model for a time series data set, which is not yet implemented in BELMAC.…”
Section: Modeling Reverberation Responsesmentioning
confidence: 99%
“…In contrast, CARAMEL utilizes a more prescriptive parameterization of BLR properties. For example, CARAMEL treats the clouds as particles that are representative of a gas density field and approximates the responding emission by setting the emissivity as a radial power-law function (Williams & Treu 2022). CARAMEL includes a parameter estimation procedure to recover the best-matching model for a time series data set, which is not yet implemented in BELMAC.…”
Section: Modeling Reverberation Responsesmentioning
confidence: 99%
“…One major class of models assumes that the BLR consists of many discrete clouds (e.g., Rees et al 1989;Baldwin et al 1995;Czerny & Hryniewicz 2011;Baskin & Laor 2018;Rosborough et al 2023). The cloud model offers advantages in flexibly parameterizing the geometry, kinematics, and photoionization physics, enabling interpretation of observations, particularly recent high-quality RM and interferometric data (Korista & Goad 2004;Pancoast et al 2011Pancoast et al , 2014aLi et al 2013Li et al , 2018Williams & Treu 2022;GRAVITY Collaboration 2018, 2020. However, the physics of the cloud model may be oversimplified.…”
Section: Broad-line Region Dynamical Model and The Inferencementioning
confidence: 99%
“…Their arguments make it clear that photoionization physics are needed in the application of RM modeling. Indeed, there has been recent progress in addressing this problem (Williams & Treu 2022;Rosborough et al 2023). Nevertheless, recent studies of NGC 3783 have shown that the modeling using GRAVITY and RM data is remarkably consistent (Bentz et al 2021b;GRAVITY Collaboration 2021a,b), which supports the application of this simple model, at least for the particular case of NGC 3783.…”
Section: Parametermentioning
confidence: 99%